2007
DOI: 10.1242/jeb.004028
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac remodelling in rainbow troutOncorhynchus mykissWalbaum in response to phenylhydrazine-induced anaemia

Abstract: Cold-acclimated fish also recovered more slowly from anaemia. In addition, warm-acclimated fish maintained compact myocardium between 32% and 37% during anaemia, while cold-acclimated fish responded with an increase in compact myocardium (from 29% to 37%). Routine cardiac output (Q) was continuously monitored following a single PHZ injection to examine the initial cardiac response to anaemia. Contrary to expectations, acute anaemia did not produce an immediate, proportionate increase in routine Q. In fact, Q d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 60 publications
3
39
0
Order By: Relevance
“…Farrell et al found that maximum in vitro performance of the sea bass heart was very sensitive to increases from 18 to 22°C, with in vitro values at 22°C being higher than we observed at 33°C in both control and anaemic fish. The rise in f H and Q are similar to previous studies on fishes (Cameron and Wohlsclag, 1969;Wood et al, 1979;Simonot and Farrell, 2007). In some species, V s also increases in anaemia, which has been linked to a prominent cardiac hypertrophy (Sun et al, 2009;Simonot and Farrell, 2007).…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Farrell et al found that maximum in vitro performance of the sea bass heart was very sensitive to increases from 18 to 22°C, with in vitro values at 22°C being higher than we observed at 33°C in both control and anaemic fish. The rise in f H and Q are similar to previous studies on fishes (Cameron and Wohlsclag, 1969;Wood et al, 1979;Simonot and Farrell, 2007). In some species, V s also increases in anaemia, which has been linked to a prominent cardiac hypertrophy (Sun et al, 2009;Simonot and Farrell, 2007).…”
Section: Resultssupporting
confidence: 88%
“…The rise in f H and Q are similar to previous studies on fishes (Cameron and Wohlsclag, 1969;Wood et al, 1979;Simonot and Farrell, 2007). In some species, V s also increases in anaemia, which has been linked to a prominent cardiac hypertrophy (Sun et al, 2009;Simonot and Farrell, 2007). It seems unlikely, however, that cardiac growth would have manifested itself within 48 h of PHZ treatment in the sea bass.…”
Section: Resultssupporting
confidence: 88%
“…Furthermore, changes detected in blood-oxygen carrying capacity may have played a role in modulating f Hmax and T HRmax with acclimation. A previous study on rainbow trout showed a strong relationship with anemia and cardiac workload and cardiac remodeling in an acclimation-temperature-dependent manner (Simonot and Farrell, 2007). This suggests the potential for alterations in cardiac parameters and cardiac workload in G. mirabilis with changes in blood-oxygen carrying capacity.…”
Section: Insights Into the Process Of Acclimationmentioning
confidence: 82%
“…While haemoglobin concentration is the primary determinant of blood oxygen carrying capacity (Gallaugher and Farrell, 1998), the present study revealed that a ∼43% decrease in haemoglobin concentration did not significantly affect metabolic attributes (SMR, MMR or AS) when compared with control fish. Previous studies on anaemic fish, with anaemia induced by experimental bleeding or intra-peritoneal injection of the haemolytic agent phenylhydrazine, have shown that they can greatly compensate for a reduced blood oxygen carrying capacity by increasing cardiac output and tissue oxygen extraction to maintain overall oxygen transport (Cameron and Davis, 1970;Simonot and Farrell, 2007). Indeed, ṀO 2 of anaemic fish during thermal ramping increased in a similar exponential manner to that in control fish and no significant differences in ṀO 2 were observed between the groups throughout the entire thermal ramping experiment.…”
Section: Reduced Blood Oxygen Carrying Capacity Does Not Affect Acutementioning
confidence: 99%